Cloning, DNA sequence, and expression of flagellins from high and low virulence strains of Edwardsiella tarda and their macrophage-stimulating activities. (March 2023) - Sun, Xiao-Mi; Yoshida, Asami; Toutani, Fukutarou; Shimizu, Takahiro; Oda, Tatsuya; Osatomi, Kiyoshi
Abstract: Edwardsiella tarda is a causative pathogen of edwardsiellosis in fish. Our previous studies on high (NUF251) and low (NUF194) virulent strains of E. tarda demonstrated that NUF251 strain induced significantly higher levels of NO and TNF-α from fish and mouse macrophages than NUF194 strain. Subsequent studies suggested that a flagellin-like protein secreted from E. tarda might be a responsible factor for the macrophage-stimulating activities. To evaluate the activities of flagellins of E. tarda, in this study, the flagellin genes of NUF251 and NUF194 strains were isolated by PCR and cloned into pQE-30 and pCold I expression vectors, and then the recombinant flagellins of two strains were overexpressed in E. coli JM109 and pG-Tf/BL21, respectively. The molecular weight of the purified recombinant flagellins of NUF251 and NUF194 strains were estimated to be 45 kDa and 37 kDa, respectively on SDS-PAGE analysis. Referring the three-dimensional structure of Salmonella flagellin, which has been reported to have 4 domains (D0, D1, D2, and D3), high sequence homology between two flagellins of E. tarda was observed at conservative domain (D0 and D1) regions, whereas the sequences equivalent to D2 and D3 domains were different, and even equivalent to 57 amino acids were deleted in NUF194. Both recombinant flagellins induced NO production, mRNA expression level of inducible NO synthase (iNOS), and intercellular ROS production in mouse macrophage cell line RAW264.7 cells. Also, the secretion of TNF-α and its mRNA expression level were increased by treatment of both recombinant flagellins. These results indicate that the recombinant flagellins from different virulent E. tarda strains can stimulate macrophages with nearly equal levels as judged by the parameters tested, even though they are differences in the structure and molecular weight, suggesting that conservative D0 and D1 domains are sufficient structural elements for the recombinant flagellins to induce a certain level of macrophage-stimulation in vitro . Further studies are necessary focusing on the role of D2 and D3 domain regions of the recombinant flagellins as macrophage-stimulating agent as well as their influence on host immune system in vivo . Highlights: We prepared recombinant flagellins of Edwardsiella tarda with different virulence. Molecular size and structure of the flagellins were different. High sequence homologies at their conservative regions were observed. The flagellins induced NO and TNF-α secretion from RAW264.7 cells similarly. Intracellular superoxide was increased in the flagellin-treated RAW264.7 cells.